Sistema de indicadores de sustentabilidade para atividade turística em espaço geográfico local: um estudo no município de Areia – PB - Lacerda, Cícero de Sousa (2019)
Sustainability indicators for tourism activity represent a tool that aims at measuring the sustainable character, as well as guiding decision makings faced with public policies that make local development feasible. For a more assertive analysis, the indicators should be selected based on the local characteristics, considering the cultural, environmental, social, economic and tourism aspects. It is also worth considering the participation of the public authority, the tourist trade, and the local society in all processes involving the indicators. When developing tourism activity using various local resources for the development of its product in a certain region, it should be monitored and evaluated to predict negative impacts and take preventive measures. These systems are tools that make it possible to monitor and establish diagnostics of the sustainability level of tourism activity. In view of the above, the following question was raised: How can a system of sustainability indicators, applied in a participatory way together with the local social actors, contribute to the tourism sustainable development in the Caminhos do Frio in the “Brejo Paraibano”? In response to this problem, this study aimed to develop a system of indicators taking into account the local characteristics of the itinerary Caminhos do Frio, in the “Brejo Paraibano”, Paraíba, Brazil. The general hypothesis of this study is that the systems of sustainability indicators, for tourism activity, developed based on local characteristics and with the participation of social actors have a better efficiency in the sustainability level identification. This is a methodological, exploratory and descriptive study, based on field research, with a qualitative-quantitative approach, in the form of a case study, with non-participant observation. In this sense, it was concluded that it was possible to develop a system of sustainability indicators to analyze the tourism activity of the itinerary Caminhos do Frio in the “Brejo Paraibano”, considering the local characteristics, through in loco visits and analysis reports of the tourism activity presented by the Tourism Company of Paraíba (PBTUR) consonant with the Brazilian Institute of Tourism (EMBRATUR), and the Atlas of Human Development of the UNDP. Based on this information, it was possible to develop a system of indicators with the following dimensions: social, environmental, economic, cultural, institutional politics, tourist services, and tourist infrastructure. From the indicators that comprise these dimensions, the definitions, justifications, objectives, measurement parameter, information source, type of measurement unit, and analysis criteria were created. To test the methodology, this sustainability indicator system was used in the municipality of Areia, which is included in the itinerary Caminhos do Frio in the “Brejo Paraibano”, with the participation of the local social actors, the tourist trade, and the public authority to evaluate the indicators. In this sense, it was possible to identify the sustainability level of the tourism activity in the municipality of Areia, where it is partially sustainable according to the social actors. It was also possible to confirm the above-mentioned hypothesis because the results of the indicators point out to a set of information that may contribute to decision makings and implementation of public policies to strengthen sustainable tourism in the itinerary Caminhos do Frio, in the “Brejo Paraibano”.